Դիտարկումներ հայերէն ձեռագրերի ԺԴ դարի առաջին քառորդի յիշատակարանների հատորի առիթով - Յովսէփեան, Լիլիթ; Ղազարեան, Դավիթ
The article stresses the importance of new publications of Armenian colophons of manuscripts, since during the decades after the first editions, various catalogues of manuscript collections, among them private ones, have appeared. This rich material should be taken into account. In 2018 the long-awaited first volume containing the colophons of the first quarter of the fourteenth century was published. It contains several times more colophons than those included in the first edition (and this was predicted by the first editor Levon Khachikyan). However, our study of the new volume has revealed a considerable number of errors and misprints which have been grouped and presented in this article in order to protect the following volumes from similar errors. В статье говорится о важности новой публикации памятных записей армянских рукописей, поскольку за прошедшие после первого издания десятилетия вышли в свет новые каталоги рукописных коллекций, в том числе и частных. Этот богатый материал должен быть учтен. В 2018 году вышел в свет долгожданный первый том, содержащий колофоны первой четверти XIV века. В него включены колофоны, число которых в несколько раз превышает вошедшие в первое издание (это было предсказано подготовившим его Левоном Хачикяном). Однако изучение тома выявило немалое количество существенных опечатков и ошибок, которые представлены в статье по группам и проанализированы с целью уберечь последущие тома памятных записей от подобных ошибок.
Keywords: Հայերէն ձեռագրերի յիշատակարաններ; Գրախոսություններ